Automatisierung des Entwurfs vollständig testbarer Schaltungen - Hellebrand, Sybille; Wunderlich, Hans-Joachim (GI - 18. Jahrestagung II, Hamburg, 1988, Informatik-Fachberichte 188)

INTEGRATED-OPTIC ROTATING WAVEPLATE FREQUENCY SHIFTER - Noé, Reinhold; SMITH, DA (ELECTRONICS LETTERS)

NEW FSK PHASE-DIVERSITY RECEIVER IN A 150 MBIT/S COHERENT OPTICAL-TRANSMISSION SYSTEM - Noé, Reinhold; SESSA, WB; WELTER, R; KAZOVSKY, LG (ELECTRONICS LETTERS)

ENDLESS POLARIZATION CONTROL-SYSTEMS FOR COHERENT OPTICS - Noé, Reinhold; HEIDRICH, H; HOFFMANN, D (JOURNAL OF LIGHTWAVE TECHNOLOGY)

INTEGRATED-OPTIC ROTATING WAVEPLATE FREQUENCY SHIFTER - Noé, Reinhold; SMITH, DA (ELECTRONICS LETTERS)

NEW FSK PHASE-DIVERSITY RECEIVER IN A 150 MBIT/S COHERENT OPTICAL-TRANSMISSION SYSTEM - Noé, Reinhold; SESSA, WB; WELTER, R; KAZOVSKY, LG (ELECTRONICS LETTERS)

ENDLESS POLARIZATION CONTROL-SYSTEMS FOR COHERENT OPTICS - Noé, Reinhold; HEIDRICH, H; HOFFMANN, D (JOURNAL OF LIGHTWAVE TECHNOLOGY)

AUTOMATIC ENDLESS POLARIZATION CONTROL WITH INTEGRATED-OPTICAL TI-LINBO3 POLARIZATION TRANSFORMERS - Noé, Reinhold; HEIDRICH, H; HOFFMANN, D (OPTICS LETTERS)

Spectrally Ordered Lie Algebras - Hilgert, Joachim (Group Theoretical Methods in Physics)

Invariant Lorentzian Orders on Simply Connected Lie Groups - Hilgert, Joachim (Arkiv för mat.)

Classification of Invariant Cones in Real Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Bull. AMS)

Invariant Cones in Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Semigroup Forum 37l. Semigroup Forum)

Representation independent query and update operations on propositional definite Horn formulas - Büning, Hans Kleine; Lettmann, Theodor (Computation Theory and Logic)

Image based SAR product simulation for analysis - Domik, Gitta; Leberl, Franz (ASPRS-ACSM)

A Hybrid Interpreter in a Software Development Environment - Engels, Gregor; Schürr, Andy (Proceedings of the 1st European Software Engineering Conference (ESEC '87), Strasbourg (France))
This paper describes the realization of an execution tool for Modula-2 modules which is part of an integrated tool set in a software development environment termed IPSEN (Incremental Programming Support Environment). In this environment, all software documents, e.g. Modula-2 modules, are manipulated by syntax-directed editors and are represented internally by attributed graphs. The execution of Modula-2 modules is done by two cooperating interpreters. The first one is a graph interpreter which traverses the internal graph from statement to statement. These statements are translated into a low-level, more efficiently executable object code and interpreted by a second interpreter. This concept of a hybrid interpreter allows the realization of an execution tool which offers a lot of runtime support features to the user.

On the Structure of Structure-Oriented Editors for Different Applications - Engels, Gregor; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the ACM SIGSOFT/SIGPLAN Software Engineering Symposium on Practical Software Development Environments, Palo Alto, USA)

Graph Grammar Engineering: A Software Specification Method - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm (Proceedings of the 3rd International Workshop on Graph-Grammars and Their Application to Computer Science, Warrenton, VA (USA))
Graphs as conceptual data models are accepted and used in a wide range of different problem areas. Giving some examples we outline common aspects for modeling complex structures by graphs. We present a formal frame-work based on graph grammars to specify graph classes and the corresponding graph manipulations. We show that such a specification can be written in a systematic, engineering-like manner. This is achieved by an extension of the known programmed, attributed graph grammars. Node-set operators are introduced to facilitate graph queries. Concepts like abstraction, decomposition, refinement, parameterization, and integration have been adopted from software engineering to yield a comprehensive specification method. This method has successfully been applied to specify the central data structures in a software development environment project

A Time-Space Tradeoff for Element Distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (SIAM Journal on Computing)

The Complexity of Parallel Sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (SIAM Journal on Computing)

Digital Rectification Method for Radar Images Applied on Huge Arrays - Domik, Gitta (Proceedings of the First Int'l. Workshop on Image Rectification Tech. for Spaceborne Synthetic Aperture Radar)